HUKUM HUMANITER INTERNASIONAL - Danial Danial (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2009)
This pape tries to explain the difference and the similarty of the law system that regulates the war law stated both in the International humanitarian law and in the Islamic law. This article will answer two main problems. First, what are the difference and the similarity of the regulation of the war law between International humanitarian law and the Islamic law? Second, to what extent is the. implementation of both International humanitarian law and the Islamic law when the war occurs?Based on the research the writer conducted, it could be concluded that: first, the similarity of the war regulation between International humanitarian law and the Islamic law covers the regulation of the beginning and the ending of the war, the method and the means used in the war time, the regulation of the war prisoner protection, the regulation of the civil society protection. In addition, both of these laws aims at humanizing the war. Moreover, the difference between International humanitarian law and the Islamic law are that while Islamic law clearly regulates the prohibition of war, the qualifications as prerequisites of war and the principle of balance, International humanitarian law do not do it so clearly that it enables a conflict tends to be a potential for war. Hence, the principles of Islamic law are appropriate to apply in, modern war condition. Second, the use of nuclear, biological and chemical weapons, ill-treatment toward war prisoners, cruel treatment and ravishment toward civil society during wars show us that the implementation of International humanitarian law has not applied completely by the parties of lawsuit in wars. Different from the implementation of Islamic law both in the Prophet era and in caliph era, in every war, the Muslim soldiers much appreciated the human values such as a very human treatment to those who did not take part in wars, the war prisoners, even to animals.